-6(x-7)+x-3=3(x+1)-22

Simple and best practice solution for -6(x-7)+x-3=3(x+1)-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-7)+x-3=3(x+1)-22 equation:


-6(x-7)+x-3=3(x+1)-22

We simplify the equation to the form, which is simple to understand
-6(x-7)+x-3=3(x+1)-22

Reorder the terms in parentheses
+(-6x+42)+x-3=3*(x+1)-22

Remove unnecessary parentheses
-6x+42+x-3=+3+*(+x+1+)-22

Reorder the terms in parentheses
-6x+42+x-3=+(+3x+3)-22

Remove unnecessary parentheses
-6x+42+x-3=+3x+3-22

We move all terms containing x to the left and all other terms to the right.
-6x+1x-3x=+3-22-42+3

We simplify left and right side of the equation.
-8x=-58

We divide both sides of the equation by -8 to get x.
x=7.25

See similar equations:

| x=1.5y^2-4 | | f(x)=-1000(3.50)+13000 | | y=-1000(3.50)+13000 | | 4x*3+5x*2-3x-1= | | -5x+x=-28 | | 4(x-1)=8(x+4) | | 8.5x=65000 | | 4(-4n-9)= | | 5+6y-25=52 | | 13(4c-7)=8c-2 | | C(x)=8.00+0.25x | | x(12.3)=1980 | | r-4+5r-4= | | 4x-12y+24=0 | | 8+4m=9m-1 | | 2+y-3=5-6x | | 4.7x-2=3.7x | | 3n+2n= | | X+6=4(2x-1) | | 6(x-3)+12+x=3(2x-6)+15+x | | X+6=4*(2x-1) | | 3(12(55))=1980 | | (2x+6)(2x-6)=-(2x+9)(3x-5) | | 3(12X)=1980 | | 180(n-2)=2700 | | ((x+4)(x+4))-4x^2+4x-1=8x | | abs(3x-2)=abs(5x+4) | | y=5(3)+7 | | m+5+7m-1= | | y=5(-4)+7 | | x+(4x+10)=230 | | y=5(0)+7 |

Equations solver categories